Compression performance of thin-walled square steel tube/bamboo plywood composite hollow columns with binding bars. Issue 3 (February 2018) - Zhao, Weifeng; Zhou, Jing; Long, Zhilin; Peng, Wanxi
A new type of thin-walled steel tube/bamboo plywood hollow composite column with binding bars was developed in which transverse binding bars were used as reinforcement. The compression performance of 12 specimens was tested to examine the failure modes of the steel tube/bamboo plywood hollow composite column with binding bars, and the influences of the slenderness ratio, the net cross-sectional area of the bamboo plywood, the load eccentricity distance, and the binding bars on the ultimate load-bearing capacity were analyzed. The results indicated that the compression failure modes of the steel tube/bamboo plywood hollow composite column with binding bars were mainly bamboo plywood material failure and debonding failure of the adhesion interface; the ultimate bearing capacity of the steel tube/bamboo plywood hollow composite column with binding bars increased with an increasing net cross-sectional area of the bamboo plywood and decreased with an increasing slenderness ratio and eccentricity distance. Transverse binding bars were introduced to ensure the integrity of the composite column, to effectively reduce the debonding failure of the adhesion interface, to change the life-limiting damage mode, and to significantly improve the load-bearing capacity of the steel tube/bamboo plywood hollow composite column with binding bars. Finite element numerical simulations were performed to extend the influential factor analysis based on the test results. Furthermore, based on a non-linear regression analysis of the experimental data, a model for calculating the load-bearing capacity was formulated to determine the allowable compressive capacity of an steel tube/bamboo plywood hollow composite column with binding bar for engineering applications.